Determinasi Aktifitas Fisik Dosen Di Wilayah Sulawesi Selatan - Haeril Haeril; Tri Angriawan (Jendela Olahraga, 2022)
This research aims at finding out the physical activity of lecturers in South Sulawesi. The research method used is survey or observation with a cross-sectional research design through a quantitative approach. Data were collected through an online questionnaire using google form. The population in this research were lecturers in South Sulawesi who were selected through the criteria of:  1) adults 25-58; 2) lecturer; 3)  being able to access the online questionnaire; and 4) willing to participate in the research. The research questionnaire was prepared to determine the determinants of physical activity using age data, walking, jogging, cycling, and gymnastic activities. The result of the research shows that the type of physical activity that is actively doing by the lecturer is walking